A comprehensive perspective on the disposition, metabolism, and pharmacokinetics of representative multi-components of Dengzhan Shengmai in rats with chronic cerebral hypoperfusion after oral administration. (10th May 2023) - Ma, Congyu; Sheng, Ning; Li, Yuanyuan; Zheng, Hao; Wang, Zhe; Zhang, Jinlan
Abstract: Ethnopharmacological relevance: Dengzhan Shengmai capsule (DZSM), an evidence-based Chinese medicine comprising Erigeron breviscapus (Vaniot) Hand. -Mazz., Panax ginseng C.A.Mey ., Ophiopogon japonicus (Thunb.) Ker Gawl., and Schisandra chinensis (Turcz.) Baill., exhibits an excellent efficacy in treating cardio- and cerebrovascular diseases. It contains caffeoyl compounds, flavonoids, saponins, and lignans as primary active components. However, so far, the characteristics of disposition, metabolism, and pharmacokinetics of its active components remain mostly unclear. Aim of study: To elucidate disposition, metabolism, and pharmacokinetics of representative components of DZSM in rats with chronic cerebral hypoperfusion (CCH) by integrating ex vivo and in situ approaches. Materials and methods: Exposure and distribution of absorbed prototypes and their metabolites were comprehensively investigated using sensitive LC-MS/MS and high-resolution LC-Q-TOF/MS. Pharmacokinetics of representative 16 components (12 prototypes and 4 metabolites) with different chemical categories, relatively high in vivo levels, wide tissue distribution, and reported neuroprotective activities were profiled. The ex vivo everted gut sac and in situ linked-rat models were adopted. Results: Representative 12 prototypes including 6 caffeoyl compounds (CA, 5-CQA, 3-CQA, 4-CQA, 1, 3-CQA, and 3, 4-CQA), 1 flavonoid (Scu), 2 saponins (Rd and Rg2), and 3 lignans (SchA, SchB, and SolA) presented characteristic absorption, disposition, and pharmacokinetics profiles in CCH rats. The caffeoyl compounds and flavonoid were well absorbed, exhibited wide distribution, and underwent extensive intestinal metabolism, such as methylation, isomerization, and sulfoconjugation. For CA, 5-CQA, Scu, and 4 related metabolites, the enterohepatic circulation was observed and resulted in bimodal or multimodal pharmacokinetic profiles. Saponins showed relatively low systemic exposure and limited distribution. The PPD-type ginsenoside Rd exhibited longer elimination half-life and systemic circulation than the PPT-type ginsenoside Rg2. No enterohepatic circulation was observed regarding saponins, suggesting that the multimodal pharmacokinetic profile of Rd could be due to its multi-site intestinal absorption. Lignans presented a low in vivo exposure and broad distribution. They were mainly transformed into hydroxylated metabolites. Corresponding to its bimodal pharmacokinetic profile, one metabolite of lignans completed the enterohepatic cycle. Conclusion: The disposition, metabolism, and pharmacokinetic profiles of representative active components of DZSM were comprehensively characterized and elucidated. Graphical abstract: Image 1 Highlights: Global characterization of DZSM prototypes and metabolites in CCH rats was achieved using LC-Q-TOF/MS and LC-MS/MS. Pharmacokinetic profiles of 16 active components in CCH rats with long-term oral administration of DZSM were reported. Intestinal absorption and enterohepatic circulation of active components were explored using ex vivo and in situ models. Enterohepatic circulation and multi-site absorption provide explanations for the bimodal pharmacokinetic profiles. The in vivo disposition and metabolic patterns of DZSM active components were visually demonstrated for the first time.